Evaluation of management practices for lentil wilt (Fusarium oxysporum f.sp. lentis) at Rampur, Chitwan, Nepal - Marahatta, Sushma; Shrestha, Sundarman; Manandhar, Hira Kaji; Aryal, Laxman; Jnawali, Arjun Dev (Journal of Agriculture and Natural Resources, 2025)
Lentil wilt is caused by Fusarium oxysporum f. sp. lentis, a major limiting factor in lentil production in Nepal. This study aimed at finding better and sustainable ways to manage it through combined biological and chemical methods. The study was done from September 2016 to March 2017 at Agriculture and Forestry University, Chitwan, Nepal. Eleven native Trichoderma isolates were tested in the lab using a dual culture method, and two fungicides, carbendazim and propiconazole, were tested for their inhibitory effects via the poison food method at concentrations of 10, 50, and 100 ppm. Field trials were conducted with seed treatment, foliar spray, and combined application in randomized complete block design with three replications. The plot size was 3 m x 3 m. Study results showed that Trichoderma isolated from Rampur and Tarahara had the highest pathogen inhibition percentage which reduces fungal growth up to 70% and 63%, respectively. Chemical carbendazim inhibited wilt mycelial growth by 86% at 10 ppm and fully at 50 ppm, while chemical propiconazole inhibited on 100 ppm fully. In the field condition, wilt disease severity was recorded lowest in the plots which were treated with combined seed and foliar applications of these chemicals but carbendazim-treated plots have the highest yield. This study highlights that combining biological control agents with chemical fungicides offers effective way to manage lentil wilt and yields. Future work should focus on reducing chemical usage by integrating resistant lentil varieties and optimized biological treatments.